2005
DOI: 10.1097/01.ccm.0000164566.23147.35
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the estimation of extravascular lung water by transpulmonary thermodilution in critically ill patients*

Abstract: In our surgical intensive care unit population, the estimation of EVLW by transpulmonary thermodilution was influenced by the amount of EVLW, the Pao2/Fio2 ratio, the tidal volume, and the level of positive end-expiratory pressure. However, compared with the double indicator method, transpulmonary thermodilution estimation remained clinically acceptable even in patients with severe lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 25 publications
0
47
0
1
Order By: Relevance
“…The significant decrease in global lung density further supports this conclusion. Scillia et al 20 revealed a significant correlation between CT derived density and EVLW by means of double indicator dilution in a canine OA model; this was confirmed later by Kuzkov et al 21 The single indicator thermodilution determination of EVLW has been validated clinically against the double indicator dilution method 16,22 and has been substantiated in animal studies against gravimetry. [23][24][25] As the PiCCO calculation of EVLW excludes both blood and tissue volumes, we anticipated lower PiCCO derived EVLW values compared with CT determined lung weights, but we expected EVLW to increase as CT lung weight increased with OA injury.…”
Section: Discussionmentioning
confidence: 86%
“…The significant decrease in global lung density further supports this conclusion. Scillia et al 20 revealed a significant correlation between CT derived density and EVLW by means of double indicator dilution in a canine OA model; this was confirmed later by Kuzkov et al 21 The single indicator thermodilution determination of EVLW has been validated clinically against the double indicator dilution method 16,22 and has been substantiated in animal studies against gravimetry. [23][24][25] As the PiCCO calculation of EVLW excludes both blood and tissue volumes, we anticipated lower PiCCO derived EVLW values compared with CT determined lung weights, but we expected EVLW to increase as CT lung weight increased with OA injury.…”
Section: Discussionmentioning
confidence: 86%
“…Although some reports have recommended pointing out pitfalls in EVLW thermodilution assessment when PHT occurs, the sensitivity of the method in this and other studies was adequate (4,29).…”
Section: Methodological Validation For the Assessment Of Evlwmentioning
confidence: 97%
“…The PiCCO algorithm allows us to estimate not only "one picture" as cardiac preload (GEDI), but also an effective functional answer (continuous CO monitoring) together with a pulmonary edema quantification (ELWI), 20,21 all of which potentially gives us the opportunity of responding rapidly to stress-related hemodynamic consequences early after SAH. 22,23 The present data demonstrated a significant impact of PiCCO CO optimization based on our goal-directed hemodynamic paradigm on DIND and vasospasm-related cerebral infarction and significantly less cardiopulmonary complications without any significant functional impact on the clinical outcome at 3 months.…”
Section: Discussionmentioning
confidence: 99%